2021
DOI: 10.3390/app11030934
|View full text |Cite
|
Sign up to set email alerts
|

Review of Dew Point Evaporative Cooling Technology for Air Conditioning Applications

Abstract: Indirect evaporative cooling has the potential to significantly improve the natural environment. It follows from a significant reduction in electricity consumption in the hot period, and hence lower operating costs for cooling systems. This paper presents the current state of knowledge and research directions on dew point indirect evaporative cooling. It was found that researchers focus on the development of dew point indirect evaporative coolers (DPIEC) by improving its design, geometry, water distribution, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The M-cycle was invented fifty years ago and revolutionized the IEC market, but it still was not investigated or described extensively. It has drawn increasing attention since 2012, and this trend can be observed in Figure 6 [34]. Before 2012, there were only a few articles and studies describing these phenomena.…”
Section: M-cycle Hvac Systemsmentioning
confidence: 98%
“…The M-cycle was invented fifty years ago and revolutionized the IEC market, but it still was not investigated or described extensively. It has drawn increasing attention since 2012, and this trend can be observed in Figure 6 [34]. Before 2012, there were only a few articles and studies describing these phenomena.…”
Section: M-cycle Hvac Systemsmentioning
confidence: 98%
“…Maisotsenko-Cycle (M-Cycle) evaporative cooling technique is an advanced method for achieving the dew point temperature as compared to the other two traditional systems where cooling limit touches the wet bulb temperature [44,48]. In this system, the cooling effect is produced by evaporative cooling and heat transfer where dew-point temperature is achieved instead of wet-bulb temperature [49,50]. Figure 6 illustrates the working principle of MEC system.…”
Section: M-cycle Evaporative Cooling (Mec)mentioning
confidence: 99%
“…Except for the aforementioned wet-bulb effectiveness, another technical term called dew point effectiveness is often applied to access the IEC system performance as shown in Equation (2) [23]: In recent years, the system performance of M-cycle IEC has been widely studied through experimental, numerical and analytical methods. Improvements in flow arrangements, geometrical size, the water distribution system and adsorbent material are the major targets in these studies [13]. Cui et al [42] introduced a configuration of M-cycle IEC simulated with CFD.…”
Section: Indirect Evaporative Cooling (Iec)mentioning
confidence: 99%
“…Although some papers have conducted reviews for the evaporative cooling technology that could be found in the literature [1,8,[13][14][15][16][17][18], there is still a lack of reviews specifically on the ECT integrated with a solid desiccant system. In this paper, recent technical developments and evaluation methods of ECT and solid desiccant-assisted evaporative cooling technologies (SDECT) were comprehensively reviewed.…”
Section: Introductionmentioning
confidence: 99%